Response of Mongolian Nomads to Climate Change during the past 800 years: Stochastic Proxies for Reconstruction - A.Orkhonselenge (Acta Mongolica, 2014)
This reviews how climate change affects the Mongolian nomadic cultures during the past over 800 years and how Mongolian Empire spreads across the Eurasia in a period of less than 100 years. Paleoclimatic proxy records imply the sunspot cycles of 11 years and glacial-interglacial transitions are predicted to have been relatively effective on rise and fall of human societies including of the Mongolian Empire and civil revolutions in Europe. Apparently, a famine that spread death and crisis across Europe is widely recorded in historical records of the early 1300s and linked to the start of the Little Ice Age. Therefore, it has been inferred to be compared climate change findings with historical accounts of famine and societal struggle in order to detect how the climate change impacted on the human societies. There would be a big challenge for Mongolian nomads for resolving how to adapt the further rising temperatures and new catastrophic events on the Earth, i.e., it requires a necessary of more empirical studies for reconstruction paleoclimate changes and of precise approaches for further predictions.